PERUKAH MEMBEDAKAN?â€ PENGALAMAN PENGASUHAN DALAM KELUARGA YANG MEMILIKI ANAK AUTISM SPECTRUM DISORDER (ASD) DAN TIPIKAL - Kristiana, Ika Febrian (Faculty of Psychology, Diponegoro University, 2016)
Caring for typical and atypical (especially autism spectrum disorder) children is not an easy task for parents. Different approaches were required to meet these two children who have differences in the characteristic of development. This was a phenomenological qualitative study aimed to describe the experience of parents caring of two children (typical and ASD). Data collection was conducted through in-depth interviews and was analyzed using data explication as one of descriptive analysis model in qualitative approach. Subjects consisted of four parents of children with typical and ASD (range from 8-12 years old). The result showed that parents provide a different approach to care for their children were typical and ASD. The decision to give a differential in parenting based on different needs and characteristics of childâ€™s development and the exsistence of supporting system (support from extended family, ex: grandmother). The examples of the differential parenting were 1) dividing the proportion of the role between fathers and mothers, where mothers concentrated on child care for ASD while fathers are more concentrated on typically child assisted by a grandmother or aunty, 2). involving typical children as siblings for ASD children in teaching a variety of developmental tasks to minimize sibling rivalry. Another interesting finding was the family's financial determine the effort of parents in providing education as part of the discharge of duties of care.